A Comparison between Emergency Medicine Residency Training Programs in the United States and Saudi Arabia from the Residents’ Perception - Khaled Alghamdi; Abdulaziz Alburaih; Mary Jo Wagner (Emergency Medicine International)
Objectives. This study was designed to compare the trainees’ perception of emergency medicine (EM) training in the United States (US) and Saudi Arabia (SA) and to identify residents’ levels of confidence and points of satisfaction in education, procedural skills, and work environment. Method. An IRB-exempt anonymous web-based survey was distributed to five EM residency training programs in the USA and three residency regions in SA. Results. 342 residents were polled with a 20% response rate (16.8% USA and 25.8% SA). The Saudi residents responded less positively to the questions about preparation for their boards’ examinations, access to multiple educational resources, and weekly academic activities. The Saudi trainees felt less competent in less common procedures than US trainees. American trainees also more strongly agree that they have more faculty interest in their education compared to the Saudi trainees. The Saudi residents see more patients per hour compared to their US peers. Conclusion. These findings may be due to the differences in training techniques including less formal didactics and simulation experience in SA and more duty hour regulations in the USA.